2014
DOI: 10.1186/1471-2296-15-65
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a semi-tailored facilitator-based intervention to optimise chronic care management in general practice: a stepped-wedge randomised controlled trial

Abstract: BackgroundThe Danish health care sector is reorganising based on disease management programmes designed to secure integrated and high quality chronic care across hospitals, general practitioners and municipalities. The disease management programmes assign a central role to general practice; and in the Capital Region of Denmark a facilitator-based intervention was undertaken to support the implementation of the programmes in general practice. The purpose of the study was to assess the effectiveness of this semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“… 42 60–67 131 132 Of the 63 intervention studies, 24 identified training facilitators. 32 37 46–48 68 69 102–107 118–120 129 133–139 Seventeen of these 24 studies described training components, with nine studies including length of training, ranging from 4 hours, 107 40 hours, 118 1–3 days 68 102 137–139 to 6–7.5 months. 32 106 Training components typically included course work (theoretical knowledge), 37 47 102 119 120 or both course work and practical experience (skills training).…”
Section: Resultsmentioning
confidence: 99%
“… 42 60–67 131 132 Of the 63 intervention studies, 24 identified training facilitators. 32 37 46–48 68 69 102–107 118–120 129 133–139 Seventeen of these 24 studies described training components, with nine studies including length of training, ranging from 4 hours, 107 40 hours, 118 1–3 days 68 102 137–139 to 6–7.5 months. 32 106 Training components typically included course work (theoretical knowledge), 37 47 102 119 120 or both course work and practical experience (skills training).…”
Section: Resultsmentioning
confidence: 99%
“…Whilst it is not clear if this is due to a lack of agreement on how to analyse the data from a SWD or because of the variety of applications of the SWD or some combination of the two, the majority of studies chose to adjust for the longitudinal nature of the SWD with either GLMMs ( n = 60, 59 %) or GEEs ( n = 17, 17 %). The remainder used a variety of methods including generalised linear models (GLM) with robust variance estimators [ 46 48 ], Cox proportional hazards modelling [ 26 , 49 – 52 ], paired t-tests [ 53 , 54 ], χ 2 tests [ 54 , 55 ], McNemar’s test [ 56 ], Wilcoxon rank sum test/Mann-Whitney U test [ 57 , 58 ], Analysis of covariance (ANCOVA) [ 58 , 59 ], Analysis of variance (ANOVA) [ 60 ], Discourse mapping [ 61 ], GLM’s with cluster as a fixed effect [ 62 – 70 ] and GLM’s without any reported effort to adjust for clustering [ 71 75 ]. For some studies the method of analysis was unclear [ 14 , 76 79 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, other pragmatic approaches to disseminate complex interventions through different levels of practice facilitation have shown mixed results. In one study of chronic care model implementation, continuous quality improvement and reflective adaption resulted in improved outcomes for all arms [30], while another stepped wedge study disseminating a chronic care model for diabetes and COPD indicated mixed results that were difficult to distinguish from concurrent initiatives [31]. A consistent result across many of these studies, including the ADAPT-NC Study, showed that patient perceptions of improved decision-making outcomes associated with the intervention were statistically significant however, significant improvements in disease outcomes between arms were harder to detect.…”
Section: Discussionmentioning
confidence: 99%
“…While practice facilitation interventions may increase time and intensity, they add value by building relationships, improving communication, fostering change, and sharing resources [32]. Practice facilitators partner with their practices to help them introduce and sustain organizational change, thereby addressing the challenges associated with implementing evidence-based guidelines into practice, a skill many practices struggle to achieve independently [31].…”
Section: Discussionmentioning
confidence: 99%